Non-contact, non-destructive mapping of thermal diffusivity and surface acoustic wave speed using transient grating spectroscopy - Reza, A; Dennett, CA; Short, MP; Waite, J; Zayachuk, Y; Magazzeni, CM; Hills, S; Hofmann, F (AIP Publishing, 2020)
We present new developments of the laser-induced transient grating spectroscopy (TGS) technique that enable the measurement of large area 2D maps of thermal diffusivity and surface acoustic wave speed. Additional capabilities include targeted measurements and the ability to accommodate samples with increased surface roughness. These new capabilities are demonstrated by recording large TGS maps of deuterium implanted tungsten, linear friction welded aerospace alloys, and high entropy alloys with a range of grain sizes. The results illustrate the ability to view the grain microstructure in elastically anisotropic samples and to detect anomalies in samples, for example, due to irradiation and previous measurements. They also point to the possibility of using TGS to quantify grain size at the surface of polycrystalline materials.